Dehydroabietylamine derived bistetrazoles from ultrasound-assisted pseudo-seven-component Ugi reactions act as efficient and selective inhibitors of cholinesterases - Niels V. Heise; Antonia Schmidt; Jördis-Ann Schüler; René Csuk (Elsevier, 2024)
The reaction of dehydroabiethylamine (DHA) with isocyanides and formaldehyde produces varying products depending on the conditions employed. In a 4-component Ugi reaction using benzyl isocyanide, paraformaldehyde, and TMS-azide, the anticipated tetrazole is formed. Nevertheless, other isocyanides were unsuccessful in these conditions. Upon substituting paraformaldehyde with formalin and utilizing ultrasound instead, bis-tetrazole formation was obtained in a pseudo-7-component reaction. A bis-benzyl-substituted tetrazole 5 demonstrated significant AChE and BChE inhibition in Ellman's assays. Molecular modeling corroborated these results, with compound 5 identified as a mixed-type inhibitor for both enzymes.